Sixteenth International Seaweed Symposium 1999
DOI: 10.1007/978-94-011-4449-0_49
|View full text |Cite
|
Sign up to set email alerts
|

Monthly changes in the content of fucans, their constituent sugars and sulphate in cultured Laminaria japonica

Abstract: Crude fucan was extracted monthly from makonbu, Laminaria japonica Areschoug, cultured from April to October at a southern site of the Hokkaido bay. The crude fucan yield tended to gradually increase from April to September, and rose markedly in October when spore formation was over. The fucans were fractionated on DEAE-Sephadex A-25 into three acidic components, A, Band C. In all the monthly extracts, fraction C was the largest. It was entirely free of laminaran and alginate, as was fraction B. Several sugars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 15 publications
3
27
0
1
Order By: Relevance
“…Seaweeds in shallow region are exposed to sunlight during low tide and so would be expected to have more amount of fucoidan as they develop defence mechanisms against dryness [24] . Since, Hare Island is characterized with shallow coastal shore with the depth of less than 1 feet, where seaweeds are often exposed to sunlight during low tide, the weeds collected from this region gave higher yields when compared to those collected from Valinokkam, which has rocky shores with depth more than 1 m. Another fact that supports this theory is that seaweeds when exposed to sunlight, their sugar content would increase and the UV rays of sunlight might destroy cellular constituents [25] .…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Seaweeds in shallow region are exposed to sunlight during low tide and so would be expected to have more amount of fucoidan as they develop defence mechanisms against dryness [24] . Since, Hare Island is characterized with shallow coastal shore with the depth of less than 1 feet, where seaweeds are often exposed to sunlight during low tide, the weeds collected from this region gave higher yields when compared to those collected from Valinokkam, which has rocky shores with depth more than 1 m. Another fact that supports this theory is that seaweeds when exposed to sunlight, their sugar content would increase and the UV rays of sunlight might destroy cellular constituents [25] .…”
Section: Resultsmentioning
confidence: 85%
“…A similar pattern was observed for other species, S. oligocystum and S. longifolium. Few studies have earlier reported that variations in the yield of fucoidan and its derivatives are affected by the season in which seaweeds are collected [25] and plant maturity [27] . The authors also reported a correlation between fucoidan yield and seasonality; and more fucoidan was obtained during the reproductive stages of the seaweed.…”
Section: Resultsmentioning
confidence: 99%
“…Fucoidan is a sulfated fucan that contains other sugars, such as galactose, xylose, and uronic acid; it mainly consists of sulfated L-fucose, which can be easily extracted from the cell wall of brown algae by hot water [15] or acid solution [16]. The molecular structure of fucoidan differs depending on the algal species [15,17], extraction process [18], season of harvest, and local climatic conditions [16,19]. Although brown algal fucoidans are complex and heterogeneous, recent structural analyses have revealed the presence of ordered repetitive fucoidan units in several species [20].…”
Section: Brown Algaementioning
confidence: 99%
“…As has been established, the content of polysaccharide in tissues of algae and its structure significantly vary during the year [2,54,72,96,102], which is supposedly determined by seasonal variations in such abiotic factors as tem perature, the concentration of mineral nutrients, and illumination [27,96]. However, there is no experimen tal evidence that these environmental factors regulate fucoidan accumulation and its compositional struc ture.…”
Section: Biosynthesis Of Fucoidans In Brown Algaementioning
confidence: 99%
“…The contents and compositional structure of sul fated polysaccharides depend on the age of algae to a significant extent. Several researchers have found a higher fucoidan content in the tissues of old algae as compared to young ones [54,111]. Moreover, old algae were shown to synthesize fucoidans with a higher fucose content than young algae do [111].…”
Section: Biosynthesis Of Fucoidans In Brown Algaementioning
confidence: 99%